Preparation and characterisation of polymer composites with bloodmeal - Clarke, Cheryl-Ann Elizabeth (University of the Free State (Qwaqwa Campus), 2016)
This research focuses on the fabrication of composites produced by the combination of BM (bloodmeal) with HOPE (high-density polyethylene). HOPE was chosen because it is amongst the most widely used synthetic plastic material worldwide, thus a study of improving the degradability of these materials can be regarded as worthwhile. HOPE was combined with dried BM. The BM was blended with the polymers using mechanical mixing at 150 °C and subsequent melt-pressing at the same temperature into films of different thicknesses. The morphology, thermal and mechanical properties, and water absorption were investi gated using moisture analysis, differential scanning calorimetry (DSC), thermogravimetric analysis (TOA), optical microscopy, scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and tensile testing before and after periods of underground ageing. Moisture analysis revealed that the addition of BM to HOPE moderately increased the moisture content of the composites. Morphological investigations showed good dispersion of BM in the polyethylene matrix, but the effects of ageing were not highly evident. DSC results indicated that the presence of BM did not significantly influence the crystallization behaviour of HOPE since the melting temperatures and melting enthalpies varied only slightly for each composition. The mechanical properties for BM composites for all ageing times showed similar trends, such as a large initial increase in modulus for I% BM added. The modulus decreased slightly as the BM content increased. Overall, the mechanical properties remained relatively constant with underground ageing time. In conclusion, it seems as if the presence of BM in HOPE had an influence on the mechanical properties and water absorption behaviour of the composites, but did not observably accelerate the underground environmental degradation of this polymer over periods as long as 36 weeks.
Keywords: Polymers; Polymeric composites; Polyethylene; Plastics -- Biodegradation; Biodegradable plastics; Dissertation (M.Sc. (Chemistry))--University of the Free State (Qwaqwa Campus), 2016